Non-invasive imaging with ICOS-targeting monoclonal antibody for preclinical diagnosis of rheumatoid arthritis in a humanized mouse model - Shao Duan; Chao Li; Feng Yan; Yifei Xia; Shuaiming Shao; Weiyu Chen; Zunyu Xiao; Gongping Xu (Journal of Translational Medicine)
Abstract Background Activated T cells play a pivotal role in rheumatoid arthritis (RA) pathogenesis, and imaging of activated T cells may provide a non-invasive tool for RA detection. Here, we first developed an optical probe targeting human inducible T cell co-stimulator (ICOS) and tested its capacity in RA diagnosis by capturing ICOS+ activated T cells in vivo in a humanized mouse model. Methods The humanized arthritis model, Human peripheral blood mononuclear cells- adjuvant induced arthritis (HuPBMC-AIA) was established, and flow cytometry and immunofluorescence were employed to determine ICOS expression in huPBMC-AIA model. Anti-human ICOS monoclonal antibody (mAb) was conjugated to Cy7 via NHS ester amine reaction. A cell uptake study was used to confirm the specificity of Cy7-ICOS mAb to activated T cells. 4-view near-infrared fluorescence (NIRF) imaging study was performed to test Cy7-ICOS mAb in detecting RA in vivo. Findings ICOS was confirmed as an indicator of RA pathogenesis via RNA-seq, flow cytometry and immunofluorescence data. An in-vitro cellular uptake study validated the specificity of Cy7-ICOS mAb to activated T cells. Cy7-ICOS mAb could detect ICOS+ activated T cells in vivo through 4-view NIRF imaging. The receiver operating characteristic (ROC) curve created based on NIRF imaging quantification could distinguish the huPBMC-AIA group from the control group at all time points imaged. Conclusion In this study, we first developed an optical imaging probe targeting human ICOS, Cy7-ICOS mAb. The 4-view NIRF imaging with Cy7-ICOS mAb could detect pathogenic ICOS+ activated T cells with high sensitivity and specificity in vivo, which indicated the great potential of this imaging probe in RA early diagnosis.